Health status and self-care of people with previous diagnosis and without diagnosis of type 2 diabetes in Mérida, México (Research, Society and Development, 2024)
Type 2 diabetes (T2DM) is a chronic disease characterized by the inefficiency of cells to utilize insulin, leading to hyperglycemia, and causing disorders in the circulatory, nervous, and immune systems, thereby damaging various organs of the body. Treatment includes healthy lifestyles, medication, and frequent monitoring. Objective: Describe the health status and self-care practices of citizens of Mérida Yucatán who live with type 2 diabetes with a previous diagnosis and without a diagnosis. Methods: Comparative, descriptive and cross-sectional study. Probabilistic sampling was carried out by clusters, the final sample was 156 adults of both sexes living with DM2. In the statistical analysis, frequencies were determined, numerical variables were categorized and the Chi-square test was used. Results: The study included 156 individuals, 84.6% (n=132) had T2DM and 15.4% (n=24) were unaware of their condition. In the previously diagnosed T2DM group, 75% had obesity, 91% had cardiovascular risk and 60% had hypertension. 37% reported high cholesterol and triglycerides levels. 91% consumed alcohol. In the undiagnosed group, 75% had obesity, 96% had cardiovascular risk, 42% had hypertension and elevated levels of cholesterol and triglycerides (29%). 83% reported alcohol intake. Conclusions: The results show health risk factors and poor self-care practices in the population even with a previous diagnosis, which underlines the need for efficient public policies.